Experience gained from using three extra oral approaches to the neck of the mandibular condyle: A comparative study - Al-Kamali, Reiadh K. (Zanco Journal of Medical Sciences (ZJMS), 2014)
Background and objective: Surgical treatment of condylar diseases involves some problems concerning the choice of the surgical approach to the condylar neck that provides adequate exposure of the area with the least trauma to the facial nerve and parotid tissue. In this paper, personal experience with the surgical treatment of some mandibular condylar neck problems by the preauricular, submandibular and the retromandibular- transmasseteric approaches is reported.Methods: Over the last 5 years, 52 condylar neck surgeries were carried out on 41 patients to treat 18 cases of condylar neck fractures, 19 cases of plate and bone graft fixation after resection of mandibular tumours and 4 cases of chronic pain and dysfunction of the TMJ. During follow-up, functions of the mandible and facial nerve branches were monitored as does the presence or absence of sialocele or parotid fistula. The appearance of the scar post- surgically and the quality of the access achieved by each type of the approaches to the condylar neck were also appraised.Results: The incidence of apparent postoperative scar appeared most after the preauricular approach to the condylar neck and least after the submandibular approach. Difficulties in management of condylar neck fractures are found more with the preauricular and least with the retromandibular-transmasseteric approaches. Weaknesses in the branches of the facial nerve are noticed in 50% of the preauricular approaches, 6.89% of the retromandibular-transmasseteric approaches, and 47.36% of the submandibular approaches. In all of the patients, this problem lasted for 3-6 weeks to resolve spontaneously thereafter. All the patients in this work suffered limitation of jaw opening in the early postsurgical period. This problem was a transient one and due to pain and muscle spasm. However, persistent limitation of jaw opening is reported in 13.79% of the retromandibular-transmasseteric approaches and 47.36% of the submandibular approaches to the mandibular condyle.Conclusion: Experience has shown that the retromandibular-transmasseteric approach to the condylar neck allows for good anatomical repositioning of the fractured condyle and direct access for precise positioning and fixation of the plate or bone graft to achieve satisfactory mandibular function with the least chance of trauma to the facial nerve and parotid tissues.